Using microstructures and TitaniQ thermobarometry of quartz sheared around garnet porphyroclasts to evaluate microstructural evolution and constrain an Alpine Fault Zone geotherm. (June 2015) - Cross, Andrew J.; Kidder, Steven; Prior, David J.
Abstract: Interpretations of deformation processes within ductile shear zones are often based on the characterisation of microstructures preserved in exhumed rocks. However, exhumed microstructures provide only a snapshot of the closing stages of deformation and we need ways of understanding how microstructures change through time and at what rate this occurs. To address this problem, we study optical microstructures and electron backscatter diffraction (EBSD) data from samples of quartz layers deflected around garnet porphyroclasts (which generate local stress and strain rate perturbations) during mylonitic deformation in the Alpine Fault Zone of New Zealand. During shearing around rigid garnet porphyroclasts, quartz undergoes grain size reduction in response to locally increased stresses, while c-axes reveal increasing components of rhomb and prism slip, reflecting a local increase in shear strain and strain rate. TitaniQ thermobarometry and quartz microstructures suggest a rather narrow range of recorded quartz deformation temperatures around 450–500 °C, which we propose reflects the cessation of grain boundary migration driven deformation. Given that temperatures well above the brittle–ductile transition for quartz (∼350 °C) are preserved, we anticipate that rapid cooling and exhumation must have occurred from the 500 °C isotherm. Ultimately, we propose a modified geotherm for the central Alpine Fault Zone hanging wall, which raises the 500 °C isotherm to 11 km depth, near the brittle–ductile transition. Our updated Alpine Fault Zone geotherm implies a hotter and weaker middle to lower crust than previously proposed. Graphical abstract: Highlights: We examine quartz sheared around rigid garnet porphyroclasts. Samples are mylonites from the Alpine Fault Zone of New Zealand. Quartz microstructures highlight locally increasing stresses and strain rates. Deformation temperatures of 450–500 °C record cessation of grain boundary migration. Temperatures used to constrain the Alpine Fault Zone geotherm and strength profile.